The Pro-Existence of Pesantren Education in Disseminating Moderate Religiosity Among Muslim Minorities - Zulihi, Zulihi; Islamy, Athoillah; Aisyah Zubaidah; Abdul Basit Atamimi (Eduprof : Islamic Education Journal, 2025)
The existence of Pesantren in the midst of Muslim minority communities poses unique challenges in terms of maintaining their continued existence.This study aims to identify the of Pesantren Darul Maarif Numbay in Jayapura City in maintaining its existence in the midst of Muslim minority life. This qualitative study in the form of a case study uses a phenomenological approach. Data was obtained through documentation, observation, and interviews. Indicators of moderate religiosity in Indonesia become the basis of perspective. This study concludes that Pesantren Darul Maarif Numbay maintains the existence of its educational continuity in the midst of Muslim minority communities through the active role of the realization of moderate religiosity by its academic community, including strengthening the value of tolerance for religious differences through the involvement of the Pesantren academic community in the Religious Communication Forum. Then, strengthening the nationalism of the education system, and an adaptive attitude towards local cultural wisdom, such as the Pesantren's adjustment to local government policies in terms of the education delivery system. Pesantren also develop local wisdom-based culture, such as the existence of al-Qur'an and Hadith subject matter on tolerance and social ethics, as well as respect for the value of traditions contained in the Rumah Honai and the tradition of Satu Tungku Tiga batu, and the tradition of Burning Stones. This study contributes to the importance of Islamic educational institutions to actively realise moderate diversity in building harmonious relations among Muslim minorities through educational, social and cultural activities. However, this study has not identified the obstacles faced by Pesantren Darul Maarif Numbay in building harmonious social relations with the Muslim minority in Jayapura. Therefore, further research is important.